A method to replace lightning strike tests by ball impacts in the design process of lightweight composite aircraft panels. (January 2018) - Soulas, F.; Espinosa, C.; Lachaud, F.; Guinard, S.; Lepetit, B.; Revel, I.; Duval, Y.
Highlights: Lightning strike induced core damage in composite panels have mechanical origin. Calculations and tests of the equivalence strategy rely on transmitted impulse. The method and hypothesis are validated using kinematics measures versus time. Lightened plates velocities and final delamination area are well reproduced. Tests highlight paint removal or maintain effects on delamination area and location. Abstract: Composite material aircrafts are protected against lightning on the basis of complex and expansive lightning strike experimental plans aiming at designing optimal protections. The paper aims at reducing the number of lightning strike tests on protected and painted composite panels. An analytical calculation is presented that gives the characteristics of an equivalent mechanical impact configuration based on an assessment of the typical time scale of energy deposit and kinematic behaviour during a lightning strike test. The paper presents our analytical hypotheses and calculations, as well as experimental lighting strikes and mechanical impact settings and results. The method is shown to give an acceptable approximation of both the kinematics and the delamination surface.